Genome-wide identification of GAD family genes suggests GhGAD6 functionally respond to Cd2+ stress in cotton - Huang, Hui; He, Yunxin; Cui, Aihua; Sun, Liangqing; Han, Mingge; Wang, Jing; Rui, Cun; Lei, Yuqian; Liu, Xiaoyu; Xu, Nan; Zhang, Hong; Zhang, Yuexin; et al. (Frontiers in Genetics, 2022)
Glutamate decarboxylase (GAD) mainly regulated the biosynthesis of γ-aminobutyric acid (GABA) and played an important role in plant growth and stress resistance. To explore the potential function of GAD in cotton growth, the genome-wide identification, structure and expression analysis of GAD genes were performed in this study. There were 10, 9, 5, and 5 GAD genes identified in G. hirsutum, G. barbadense, G. arboreum, and G. raimondii, respectively. GAD was divided into 4 clades according to protein motifs composition, gene structure, and phylogenetic relationship. The segmental duplication was the main way of the GAD gene family evolutionary. Most GhGADs respond to abiotic stress. Clade Ⅲ GAD was induced by Cd2+ stress, especially GhGAD6, and silencing GhGAD6 will lead to more serious Cd2+ poisoning in cotton. The oxidative damage caused by Cd2+ stress was relieved by increasing GABA content, it was speculated that the decreased expression of GhGAD6 reduced the content of GABA in vivo, and caused the accumulation of ROS. This study will further expand our understanding of the relationship between the evolution and function of the GhGAD gene family and provide new genetic resources for cotton breeding under environmental stress and phytoremediation.